Occupational stress of Bank of the Philippine Islands employees in the Province of La Union - Valdez, Rosher Xantina A. (Saint Louis College : [s.n.], 2021)
This study aimed to address the occupational stress on the job performance of Bank of Philippine Island (BPI) employees in the Province of La Union as basis of a proposed stress management program for BPI employees. It used the descriptive-correlational method of research and involved a total of 45 BPI employees as the respondents. A research-made questionnaire was used in gathering the data. The data gathered were treated using frequencies and percentages, correlation analysis, and multiple regression. The study found that the BP Officers were composed of married male and female college graduates who were within several age brackets and whose length of service fell under various year brackets while the rank and file employees are single and female college graduates in great majority who were a mixture of several age brackets and who had been in the service for 1-5 years and more. The BPI employees were sometimes stressed in their occupation. Specifically, they were often stressed by their job demands while they were seldom stressed by their social support and work environment. There is no significant relationship between the personal profile of the respondent and their level of stress. A stress management program crafted by the researcher was proposed to help minimize the stress suffered by respondent BPI employees. It was concluded that the BPI employees possess personal and professional qualifications in performing their jobs. The BPI employees are still young in the banking industry and find their occupation less bothersome. The personal profile of the respondent does not influence their level of stress. It is recommended that the stress management program should be adopted to help minimize the stress suffered by respondent BPI employees.
References: pages 94-103
CHED-La Union
Keywords: Stress management